Systemic Erysipelas Outbreak among Free-Ranging Bottlenose Dolphins, San Diego, California, USA, 2022 - Kerri Danil; Kathleen M. Colegrove; Martha A. Delaney; Alexandria Mena; Nancy Stedman; Elyse Wurster (Emerging Infectious Diseases, 2023)
We diagnosed fatal Erysipelothrix rhusiopathiae sepsis in 3 stranded bottlenose dolphins (Tursiops truncatus) during summer 2022, in San Diego, California, USA. The previously undetected disease in this relatively small, regional population of dolphins most likely indicates an environmental or biological change in the coastal ocean or organisms.